Implementasi Metode Profile Matching Pada Sistem Pendukung Keputusan Pemilihan Distributor Alat Kesehatan - Nuraini, Rini (Politeknik Harapan Bersama, 2022)
Utilization of information technology in a company will assist in increasing the productivity of the company in carrying out its duties and responsibilities. Distributors are the most important part in a company that provides medical equipment in obtaining goods for the sustainability of the company. The evaluation process for distributors currently does not use a system, so the company has difficulty in evaluating distributors from the requirements that will be calculated and used as material for evaluating the distributor's performance. The decision support system in the selection of this distributor uses profile matching. Profile matching is a method in a decision support system that will provide recommendations based on a comparison of the profiles of each distributor with the highest score. The decision support system for selecting Medical device distributors helps companies to automate and computerize in determining the performance of distributors in meeting company needs. The results of manual calculations and web applications on the selection of medical device distributors show the same results, and there are no different calculations. Test results using blackbox get perfect results, namely 100% for all system functions created for the selection of medical device distributors